The Dead - George Pavlakis (Pathogens and Immunity)
George N. Pavlakis, MD, PhD, has published (in Greek) a collection of poems as well as memoirs from the years of students’ resistance against the Greek military dictatorship (1967-1974). The poem “The Dead” is part of the published collection (Fairy Tales of the Past) and suggests Odyssey’s Nekyia, by Homer, where Odysseus goes to the underworld to meet Prophet Teiresias. Following instructions, Odysseus sacrifices an animal and is surrounded by many blood-thirsty ghosts, including his mother’s.